Hubungan Tingkat Pengetahuan Mahasiswa Universitas Islam Negeri Sumatera Utara Fakultas Kesehatan Masyarakat Terhadap Kebiasaan Merokok - Anggun Triyoolanda (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Smoking is a behavior that has a negative impact on both health and the environment. Smoking behavior occurs in various groups, even students who are individuals with a high level of education. In an effort to quit smoking behavior, a smoker must have strong motivation, one of the factors that can affect a person's motivation is knowledge. The purpose of this study was to determine the relationship between the level of knowledge about the impact of smoking on oral health and the level of motivation to stop smoking. This research method was carried out using analytic correlation using a cross sectional design. All data obtained were analyzed using the chi-square statistical test. The results of statistical tests in this study showed that the p-value (0.000) <0.05, meaning that there is a relationship between the level of knowledge and motivation to stop smoking. This indicates that the higher the level of knowledge, the higher the motivation to stop smoking. Based on the results of the research that has been done, it can be concluded that there is a significant relationship between the level of knowledge of the impact of smoking on the oral cavity and the level of motivation to stop smoking among students at Maranatha Christian University.